PENGARUH HARI PERDAGANGAN TERHADAP RETURN SAHAM PERUSAHAAN YANG TERDAFTAR PADA INDEKS LQ 45 BURSA EFEK INDONESIA - Siahaan, Roy; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2020)
This research aims to determine the effect of trading days, Monday effects and weekend effects on the average daily return value of companies listed on the LQ 45 index of the Indonesia Stock Exchange from February 2018 to January 2020. The population in this study consisted of 633 listed companies on the Indonesia Stock Exchange and the sample consists of 33 companies that meet the sample criteria obtained using purposive sampling techniques from February 2018 to January 2020. Data on daily stock return values ​​are obtained through www.yahoofinance.com and www.idx.co.id. To test the effect of trading days on the value of stock returns used a simultaneous test (f-test) and to test the effect of the Monday effect and weekend effect on the value of stock returns used a partial test (t-test). The results showed that there was no significant effect by trading day on the value of LQ 45 stock returns of the Indonesia Stock Exchange from February 2018 to January 2020 and there was no significant effect by Monday effect and weekend effect on the value of LQ 45 corporate stock returns of the Indonesia Stock Exchange the period February 2018 to January 2020. Keywords: LQ 45; Monday Effect; Stock Returns; Trading Days; Weekend Effect.